An evidence-based framework for reducing occupational stress and burnout in Pakistani Universities / Naima Akhtar Malik and Kaj Björkqvist - Akhtar Malik, Naima; Björkqvist, Kaj (Universiti Teknologi MARA, 2021)
The aim of the study was to design a framework for university administrations to provide guideline for the effective management of the issues of occupational stress and burnout among university teachers in Pakistan. A total of 320 university teachers participated in the study. Of the respondents, 144 (45%) were female, and 176 (55%) were male. The questionnaire was especially constructed for the study and it comprised six subscales. The results showed that there was no significant gender difference between the scores of the respondents except on one scale. The results show that university teachers are not satisfied with the efforts made by university administrations to deal with problems of occupational stress and burnout. In the light of the results, a framework has been designed for university administrations in Pakistan.